2006
DOI: 10.1097/01.mlg.0000244387.11129.a0
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up for Children Treated With Surgical Intervention for Chronic Rhinosinusitis

Abstract: Children who have chronic rhinosinusitis improve in their symptoms of nasal airway obstruction and purulent discharge if they undergo surgery. Parents of young children with chronic rhinosinusitis appear to be more satisfied with the outcome of surgical management than medical management when assessed 10 years later.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 78 publications
0
21
0
2
Order By: Relevance
“…The results of FESS due to CRS in children have been shown in several studies [18,21,24,38]. Most of the reported outcomes are based on the levels of symptomatic relief and do not include objective measures such as nasal endoscopy or CT scans.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The results of FESS due to CRS in children have been shown in several studies [18,21,24,38]. Most of the reported outcomes are based on the levels of symptomatic relief and do not include objective measures such as nasal endoscopy or CT scans.…”
Section: Discussionmentioning
confidence: 96%
“…FESS is unlike to be successful in children below the age of three [45]. But Lusk et al reported a 10-year retrospective study, which proved superiority (p > 0.001) of FESS in the age of 2-5 years over medical treatment in parenteral assessment of improvement [38]. Efficiency of FESS has been found to be reduced if a child is exposed to tobacco smoke [44].…”
Section: Discussionmentioning
confidence: 96%
“…Conjunctive consolidation has been used to develop grading systems for lung cancer, 30 head and neck cancer, 31, 32 obstructive sleep apnea, 25 and rhinosinusitis. 33 , and is particularly useful for combining independent indices into a composite measure. Based on the conjunctive consolidation approach, neuroimaging information did not alter outcome predictions for patients with favorable clinical presentations.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical drainage of the abscess was afforded with FESS. This transnasal endoscopic technique provided a quick and safe drainage of the paranasal sinuses, orbita, anterior skull base avoiding facial scars as well as hastening the post-operative recovery period [11,12]. Rahbar et al found that orbital subperiosteal abscess in children can be successfully and safely managed by a transnasal endoscopic approach in selected patients [6].…”
Section: Discussionmentioning
confidence: 99%